Italy at the polls. Four lessons to learn from the 2022 general election. Issue 1 (2nd January 2023) - Chiaramonte, Alessandro
ABSTRACT: On 25 September 2022, in an election that saw a record low turnout, the coalition of the centre-right emerged as the clear winner and Fratelli d'Italia (FdI) as the most-voted party. As a result, the centre-right political forces agreed to form a government headed by FdI's leader, Giorgia Meloni, who became the first female Prime Minister in Italy's history. The aim of this article is to gain a better understanding of the election outcome and of its implications for the transformation of the Italian party system. The main 'lessons' of the results have to do with voters increasingly dissatisfied with parties and prone to abstaining or to changing their vote choice, and with a party system that has become more polarized and de-institutionalized.